Enhancing Women's Role in the Biotechnological Utilization of Usar Soils - Bhadauria, Seema; Chauhan, B. P. S.; Singh, Archna; Pahari, Gautam; Verma, Sudhir (Indian Forester, 1999)
The biotechnological utilization of usar soil project in the Ishwarpur village of Mainpuri District in U.P. aims to reclaim the usar soil of village Ishwarpur by giving technical training and educating the women. Women being the primary collectors of fodder, firewood and other produce from the common lands, have a greater stake in its rehabilitation and a major role in its conservation and management. This paper describes why and how to obtain involvement of the rural women in these activities. It also presents the approaches adopted, the challenges faced and progress made in involvement of women in development programmes by the project.